IMPLEMENTASI PERWALI SURABAYA NO. 5 TAHUN 2013 TENTANG PEDOMAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Dida Rahmadanik; Nurul Ika Mardiyanti; Indah Murti (REFORMASI, 2022)
Based on the Surabaya Mayor Regulation Number 5 of 2013 concerning Guidelines for the Use of Information and Communication Technology in the Implementation of Regional Government, that in each agency making innovations which utilizes information and communication technology in providing services based on convenience for users; without barriers between one institution and another; transparent and the availability of public information; fairness; accountable; and service standardization. But in reality many teachers have difficulty in using it. This study aims to describe the application of the SIAGUS application at SMPN 52 Surabaya along with its supporting and inhibiting factors. This type of research is using descriptive qualitative. The focus of his research uses the theory of indicators of successful implementation of e-government based on the results of a study from the Harvard JFK School of Government namely Support, Capacity, and Value. The results of this study indicate that the application of the SIAGUS application at SMPN 52 Surabaya is quite good when viewed from the indicators of Support, Capacity, and Value but there are still teachers who do not understand how to use the SIAGUS application so that in-depth assistance is needed by forming small groups and additional appointments. operators to be included in the group. In addition, server errors were also encountered so that there was a need for repairs or additional capacity on the central server at the Surabaya City Education Office.AbstrakBerdasarkan Peraturan Walikota Surabaya Nomor 5 Tahun 2013 tentang Pedoman Pemanfaatan Teknologi Informasi dan Komunikasi dalam Penyelenggaraan Pemerintahan Daerah bahwa dalam tiap instansi membuat inovasi yang memanfaatkan teknologi informasi dan komunikasi dalam memberikan pelayanan yang berasaskan pada kemudahan bagi pemgguna; tanpa jarak antara satu instansi dengan instansi lain. Namun pada kenyataannya banyak guru yang mengalami kesulitan dalam menggunakannya. Penelitian ini bertujuan untuk mendeskripsikan mengenai penerapan aplikasi SIAGUS di SMPN 52 Surabaya berserta dengan faktor pendukung dan penghambatnya. Jenis penelitian ini menggunakan deskriptif kualitatif. Fokus penelitiannya menggunakan teori indikator keberhasilan penerapan e-government berdasarkan hasil kajian dari Harvard JFK School of Government yaitu Support, Capacity, dan Value. Hasil penelitian ini menunjukkan bahwa penerapan aplikasi SIAGUS di SMPN 52 Surabaya cukup baik apabila dilihat dari indikator Support, Capacity, dan Value namun juga masih ditemukan guru yang kurang paham dalam menggunakan aplikasi SIAGUS sehingga perlu dilakukan pendampingan secara mendalam dengan cara membentuk kelompok kecil dan penunjukan tambahan operator untuk dimasukkan ke dalam kelompok tersebut. Selain itu juga ditemui server eror sehingga perlu adanya perbaikan atau penambahan kapasitas pada server pusat di Dinas Pendidikan Kota Surabaya.